2022
DOI: 10.3389/fphy.2022.943520
|View full text |Cite
|
Sign up to set email alerts
|

Systemic risk of multi-layer financial network system under macroeconomic fluctuations

Abstract: As the global economy continues to integrate, COVID-19 is affecting businesses around the world, causing the financial system to become more complicated. The complicated relationship between various agents in the financial system makes potential hazards more easily transmitted. Most studies of systemic risks have focused on single-layer networks, and macroeconomic fluctuations have not been quantified in multi-layer models of financial networks. In this paper, three different macroeconomic shock scenarios (sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The study shows that banks contribute to their stability by selling depreciating assets, and investment risk is an uncertainty that affects the stability of banks. In their work, Lux [ 34 ], Silva et al [ 35 ], and Gao et al [ 36 ] constructed the multi-layer financial network system based on interbank and bank–firm networks. Based on De Masi and Gallegati’s research on the actual data sets of Italy and Japan [ 37 ], Lux [ 34 ] proposed a generation algorithm for the bilateral bank–firm network and combined it with the interbank network to study risk contagion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study shows that banks contribute to their stability by selling depreciating assets, and investment risk is an uncertainty that affects the stability of banks. In their work, Lux [ 34 ], Silva et al [ 35 ], and Gao et al [ 36 ] constructed the multi-layer financial network system based on interbank and bank–firm networks. Based on De Masi and Gallegati’s research on the actual data sets of Italy and Japan [ 37 ], Lux [ 34 ] proposed a generation algorithm for the bilateral bank–firm network and combined it with the interbank network to study risk contagion.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the network structure of the financial system plays an important role in the contagion of risk. Gao et al [ 36 ] studied the systemic risk of the multi-layer financial network system under macroeconomic fluctuations and found that firms with medium and high leverage and small asset sizes, as well as banks with smaller asset sizes and fewer bank–firm credit links, are more likely to default. On the assumption that banks do not recover loans from firms, Chen et al [ 38 ] constructed a two-layer credit risk contagion network model between banks and firm counterparties.…”
Section: Introductionmentioning
confidence: 99%